REINTERPRETASI HADIS PERINTAH “MEMBUNUH MANUSIA SAMPAI MENGUCAP SYAHADAT” SEBAGAI UPAYA DERADIKALISASI AGAMA - Muhammad Mundzir (IAIN Tulungagung, 2019)
Starting from radicalism in Indonesia in the name of Islam, this paper tries to describe how the hadith is understood about